„Szaty ze skór”: kara czy ratunek dla człowieka? Patrystyczna interpretacja Rdz 3, 21 - Naumowicz, Józef (Vox Patrum, 2010)
In giving different allegorical meanings to the „garments of skins” (Gen 3:21) given to man after the Fall (mortality, corporeality, carnal mentality, animality, passions), the patristic authors tried not only to describe the effects of the sin of the first people, but also and above all to show what God did to ensure that the consequences of the Fall did not last forever and that a return to paradise might be possible. What most interested them was the meaning of these garments in the history of salvation. So Irenaeus of Lyon formed the concept of these garments as an antidote or medicine for sin, a concept developed later by the Cappadocian fathers. Gregory of Nyssa emphasized the fact that they permitted the preservation of man’s freedom and other characteristics of his having been formed in the image of God (rationality). In short, they were given in order to open a road for man to God, to make possible a return to paradise. Even if they signify the effects of the fall of man, which effects can be held to be burdensome and trying, they are not an expression of the Creator’s anger and punishment, but rather deliverance for man and a chance of salvation. They can at most be considered as „a divine way of punishing”, which is ultimately „a manifestation of mercy” (Gregory of Nazianzen).